Synergistic enhancement of ectopic bone formation by supplementation of freshly isolated marrow cells with purified MSC in collagen–chitosan hydrogel microbeads. (1st November 2016) - Wise, Joel K.; Alford, Andrea I.; Goldstein, Steven A.; Stegemann, Jan P.
ABSTRACT: Purpose: Bone marrow-derived mesenchymal stem cells (MSC) can differentiate osteogenic lineages, but their tissue regeneration ability is inconsistent. The bone marrow mononuclear cell (BMMC) fraction of adult bone marrow contains a variety of progenitor cells that may potentiate tissue regeneration. This study examined the utility of BMMC, both alone and in combination with purified MSC, as a cell source for bone regeneration. Methods: Fresh BMMC, culture-expanded MSC, and a combination of BMMC and MSC were encapsulated in collagen–chitosan hydrogel microbeads for pre-culture and minimally invasive delivery. Microbeads were cultured in growth medium for 3 days, and then in either growth or osteogenic medium for 17 days prior to subcutaneous injection in the rat dorsum. Results: MSC remained viable in microbeads over 17 days in pre-culture, while some of the BMMC fraction were nonviable. After 5 weeks of implantation, microCT and histology showed that supplementation of BMMC with MSC produced a strong synergistic effect on the volume of ectopic bone formation, compared to either cell source alone. Microbeads containing only fresh BMMC or only cultured MSC maintained in osteogenic medium resulted in more bone formation than their counterparts cultured in growth medium. Histological staining showed evidence of residual microbead matrix in undifferentiated samples and indications of more advanced tissue remodeling in differentiated samples. Conclusions: These data suggest that components of the BMMC fraction can act synergistically with predifferentiated MSC to potentiate ectopic bone formation. The microbead system may have utility in delivering desired cell populations in bone regeneration applications.